2021
DOI: 10.3389/fonc.2021.788875
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Vaccine Alone and in Combination With an Immune Checkpoint Antibody Inhibits Growth and Metastases of Gastric Cancer

Abstract: Gastric cancer is a leading cause of cancer-related deaths worldwide. Recently, clinical studies have demonstrated that many of those with advanced gastric cancer are responsive to immune checkpoint antibody therapy, although the median survival even with these new agents is less than 12 months for advanced disease. The gastrointestinal peptide gastrin has been shown to stimulate growth of gastric cancer in a paracrine and autocrine fashion through the cholecystokinin-B receptor (CCK-BR), a receptor that is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…For instance, researchers created an injectable hydrogel that can shear-thin and is loaded with polyphyllin II and resiquimod, which can help potentiate localized immunotherapy of GC by repolarizing TAMs[ 78 ]. Polyclonal antibody stimulator monotherapy or combined with PD-1 antibody[ 79 ], as well as using a natural alkaloid product isolated from sophora alopecuroides. L, sophoridine[ 80 ], may decrease the number of immunosuppressive M2-polarized TAMs.…”
Section: Tams and Targeted Therapies Of Digestive System Malignant Tu...mentioning
confidence: 99%
“…For instance, researchers created an injectable hydrogel that can shear-thin and is loaded with polyphyllin II and resiquimod, which can help potentiate localized immunotherapy of GC by repolarizing TAMs[ 78 ]. Polyclonal antibody stimulator monotherapy or combined with PD-1 antibody[ 79 ], as well as using a natural alkaloid product isolated from sophora alopecuroides. L, sophoridine[ 80 ], may decrease the number of immunosuppressive M2-polarized TAMs.…”
Section: Tams and Targeted Therapies Of Digestive System Malignant Tu...mentioning
confidence: 99%
“…15 Additionally, Smith et al reported that gastrin vaccine alone or combined with PD-1 antibody restrained GC growth and metastasis by reducing the M2 TAMs in the TME. 153 Researchers used CD40-HER2 bispecific antibody to target CD40 and maintain the ubiquitination level of TRAF6/3, thereby increasing its degradation in macrophages and consequently activating the NF-κB pathway to increase M1 TAMs and offset trastuzumab resistance in HER2-positive GC cells. 16 Furthermore, Guo et al reported that dextran sulphate reduced the promoting effects of M2 TAMs on the angiogenesis, and migratory and invasive abilities of GC cells using co-culture assays.…”
Section: Targeting Tams In Immunotherapymentioning
confidence: 99%
“…Although cancer vaccine has shown favourable benefits in phase I and phase II trials against advanced gastric cancer, its clinical efficacy is low because of regulation and suppression from the host immune system. Novel strategies to overcome this limitation involve the development of combined therapies, for example, combination of cancer vaccine and immune modulator to avoid immune suppression, use of conventional chemotherapy in addition to cancer vaccine to enhance anti-tumour activity but reduce cytotoxicity (66).…”
Section: Challenges and Potential Strategiesmentioning
confidence: 99%